2012
DOI: 10.1111/j.1755-3768.2012.t025.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor‐1a (HIF‐1a) and Heat Shock Proteins 90, 70 (HSP 90, 70) expression in ocular pterygium and normal conjunctiva.

Abstract: Purpose Research has shown that HSPs participates in preserving HIF‐1a function. In this study, HIF‐1a, and HSP90, 70, expression and immunolocalization in ocular pterygium and normal conjunctiva samples was examined. Methods Fifty nine samples of ocular pterygium and twenty samples of normal conjunctiva, surgically removed, were tested with immunohistochemistry, immunofluorecense and western blot analysis. Results Between pterygium specimens and normal conjuctiva specimens, significant differences were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…Using geldamycin, an inhibitor of Hsp90, the authors demonstrated that Hsp90 is important as a molecular chaperone in CB2 receptor-mediated cell signaling and actin cytoskeleton rearrangement in trabecular meshwork cells ( 58 ). In our previous study ( 59 ) the abundant expression of Hsp90 in pterygial epithelial cells was displayed in contrast to that in conjunctival cells. In addition, correlation analysis revealed that Hsp90 expression is significantly correlated with the expression of CB2 receptor (Spearman's rho=0.660; P<0.01) in pterygium samples, but not in conjunctiva (P>0.05).…”
Section: Discussionmentioning
confidence: 79%
“…Using geldamycin, an inhibitor of Hsp90, the authors demonstrated that Hsp90 is important as a molecular chaperone in CB2 receptor-mediated cell signaling and actin cytoskeleton rearrangement in trabecular meshwork cells ( 58 ). In our previous study ( 59 ) the abundant expression of Hsp90 in pterygial epithelial cells was displayed in contrast to that in conjunctival cells. In addition, correlation analysis revealed that Hsp90 expression is significantly correlated with the expression of CB2 receptor (Spearman's rho=0.660; P<0.01) in pterygium samples, but not in conjunctiva (P>0.05).…”
Section: Discussionmentioning
confidence: 79%
“…A coordinated activation and increase of HIF-1α and heat shock proteins in pterygium, may represent an adaptive process for the survival of cells undergoing stressful conditions [32].…”
Section: Discussionmentioning
confidence: 99%
“…In pterygium, increased expression of Hsp27 was significantly found in the epithelial, endothelial, and conjunctival vascular smooth muscle cells. In addition, an elevation in the expression of Hsp70 and Hsp90, as well as an alteration of hypoxia-inducible factor-1α (HIF-1α), was also found to induce the mechanism of pterygium [32].…”
Section: H Heat Shock Proteinsmentioning
confidence: 99%